2019
DOI: 10.1136/bmjopen-2019-032631
|View full text |Cite
|
Sign up to set email alerts
|

Which orthopaedic trauma patients are likely to refuse to participate in a clinical trial? A latent class analysis

Abstract: ObjectiveThe study aimed to assess systematic differences in the characteristics of patients that consented for the trial compared with the broader pool of eligible patients in a large, pragmatic orthopaedic trauma trial.DesignA retrospective observational study performed from April 2017 to March 2018.SettingAcademic trauma centre in Baltimore, USA.ParticipantsThere were 642 eligible adult trial participants with an operative fracture to the appendicular skeleton and were indicated for blood clot prophylaxis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Investigators might also consider the amount of follow-up time required, the burden of data collection, patient incentives, and the amount of time the patient has to decide whether to participate or not. O'Hara et al 3 also found that the specific intervention was related to consent rates, with prophylactic medication regimens having higher refusal rates than surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators might also consider the amount of follow-up time required, the burden of data collection, patient incentives, and the amount of time the patient has to decide whether to participate or not. O'Hara et al 3 also found that the specific intervention was related to consent rates, with prophylactic medication regimens having higher refusal rates than surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of recruitment are infrequently published in the orthopaedic literature; those that are range dramatically from 10% to 92%. In the United States and Canada specifically, the rate of participation 2,3 is lower than other countries (80%) and below 50% when studies are randomizing to an operative versus a nonoperative arm. 2 However, some literature seems to demonstrate that participation in clinical trials is higher among patients with orthopaedic trauma as compared with other subspecialties, with participation above 85%.…”
Section: Introductionmentioning
confidence: 97%
“…Exclusion criteria were (1). age of participants not specified (with the exception of studies that used age of 65 years or above as an inclusion criterion, these were included even if age of the population was not specified), (2). study population not adequately described to determine eligibility using the inclusion criteria, and (3).…”
Section: Article Screening For Eligibilitymentioning
confidence: 99%
“…The inclusion criteria were (1). clinical studies (ie, RCTs, prospective cohort studies including nonrandomized clinical trials, retrospective cohort, cross-sectional, or cohort studies not otherwise specified), (2). studying patients with fracture with a median or mean age of 65 years and above, and (3).…”
Section: Article Screening For Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation